2022
DOI: 10.1039/d2tb00571a
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Prussian blue nanoparticles for modulating polyethyleneimine cytotoxicity and attenuating tumor hypoxia for dual-enhanced photodynamic therapy

Abstract: Photodynamic therapy (PDT) is a promising cancer therapy modality due to its intrinsically negligible side effects and treatment resistance. However, the development of the high-efficiency PDT still remains a challenge....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Besides, better therapeutic efficacy was observed in breast cancer cells and tumor-bearing mice after laser irradiation. 51 In another study, evident cell apoptosis and necrosis were observed in PEGylated nanographene oxide-treated cancer cells and this study is an example of combination therapy. 52 A recently published paper examined an iron-dependent regulated cell death process (ferroptosis) by liposomes embedded with PEG-coated 3 nm γ-Fe 2 O 3 nanoparticles in the bilayer.…”
Section: Mechanism Of Targeting By Nano Drug Vehiclesmentioning
confidence: 60%
“…Besides, better therapeutic efficacy was observed in breast cancer cells and tumor-bearing mice after laser irradiation. 51 In another study, evident cell apoptosis and necrosis were observed in PEGylated nanographene oxide-treated cancer cells and this study is an example of combination therapy. 52 A recently published paper examined an iron-dependent regulated cell death process (ferroptosis) by liposomes embedded with PEG-coated 3 nm γ-Fe 2 O 3 nanoparticles in the bilayer.…”
Section: Mechanism Of Targeting By Nano Drug Vehiclesmentioning
confidence: 60%
“…S1c,† the fine energy spectrum of O 1s had two absorption peaks at 531.9 eV and 533.4 eV, attributing to the CO and the binding energy of the C–O bond, respectively. 34 In the fine energy spectrum of Fe 2p (Fig. S1d†), five characteristic peaks were observed at 708 eV, 710.1 eV, 712.3 eV, 721.5 eV, and 724.4 eV, respectively, which were attributed to Fe–N, Fe 2+ 2p 3/2 , Fe 3+ 2p 3/2 , Fe 2+ 2p 1/2 and Fe 3+ 2p 1/2 .…”
Section: Resultsmentioning
confidence: 99%
“…PEI-based drug delivery systems are also used for other therapies, such as photothermal therapy (PTT), photodynamic therapy (PDT), immunotherapy, and combination therapy [ 159 , 160 , 161 , 162 , 163 , 164 ]. For example, Huang et al reported that PEI-coated oxidized mesoporous carbon nanospheres were designed for combined PTT and gene therapy of tumors [ 154 ].…”
Section: Pei-based Drug Delivery Systemsmentioning
confidence: 99%